Do 90 percent of terrorist groups last less than a year?: Updating the conventional wisdom - Phillips, Brian J. (Terrorism and political violence, 2019)
Prominent scholars criticize terrorism research for lacking sufficient empirical testing of arguments. Interestingly, one of the most widely cited estimates in terrorism studies has not been evaluated using the many data sources now available. Rapoport’s 1992 claim, that perhaps 90 percent of terrorist groups last less than one year, has been described as part of the conventional wisdom. This estimate is frequently used to justify studies of terrorist group longevity, a substantial line of research in recent years. Is the estimate accurate? Scholars increasingly publish data sets of terrorist organizations, but no one has analyzed them collectively to see if the 90 percent claim holds up. This article examines the eight largest global data sets of terrorist group longevity, covering 1968–2013. The samples vary considerably, but the percentage of groups that do not survive beyond their first year in these relevant data sets is between 25–74 percent. Across all data sets, on average about 50 percent of terrorist organizations do not make it past their first year. There is some variation depending on group motivations, consistent with Rapoport’s “wave” theory. However, overall, terrorist organizations appear to be more durable than the conventional wisdom suggests.